Penerapan Pelaporan Dan Penyajian Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah (SAK EMKM) - Wigiyanti; Ashar Basyir (Forum Kerjasama Pendidikan Tinggi, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the country's economy so there is a need to empower and improve the MSME system. MSMEs are still focused on their operational activities so that financial recording and reporting is neglected. The Financial Accounting Standards Board-Indonesian Accountants Association (DSAK-IAI) has prepared Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) to help MSMEs achieve financial literacy, as well as optimize opportunities and maximize their business performance. The objectives of this research are; understand the reporting and presentation of the implementation of Financial Accounting Standards for Micro, Small and Medium Entities at Wesh Wash Laundry. This researcher used a descriptive qualitative approach. Data collection techniques through observation, interviews, documentation and literature study. In implementing reporting and presentation based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM). Based on research results, MSME business actors have not fully implemented reporting and presentation based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM), there are several account items that are not recorded and are not presented in the company's financial reporting.